Neurophysiological signatures of Stanford Neuromodulation Therapy in treatment resistant depression - Davide Momi; Derrick M. Buchanan; Masataka Wada; Andrew D. Geoly; Noriah J. Johnson; Eleanor J. Cole; Adi Maron-Katz; Claudia Tischler; Christopher C. Cline; Diego A. Pizzagalli; Manish Saggar; Daphne Voineskos; et al. (Molecular Psychiatry, 2026)
Abstract Treatment-resistant depression (TRD) affects approximately 30% of patients with major depressive disorder. Stanford Neuromodulation Therapy (SNT), a high-dose intermittent theta-burst transcranial magnetic stimulation protocol, produces rapid antidepressant effects, but its neurophysiological mechanisms remain unclear. Here, we used longitudinal TMS-EEG to characterize the progressive neurophysiological changes induced by SNT, assess their site-specificity, and explore whether baseline neural markers are associated with clinical response. We conducted a double-blind, randomized, sham-controlled trial at Stanford University (2017–2018; analysis August 2024–October 2025) in 24 TMS-naïve participants with TRD (Montgomery-Åsberg Depression Rating Scale ≥20; ≥1 failed antidepressant trial). Participants were randomized to active (n = 12) or sham (n = 12) SNT, consisting of 10 sessions per day over 5 consecutive days targeting the left dorsolateral prefrontal cortex (90,000 pulses). TMS-EEG was acquired at two baseline sessions, before and after each treatment session, and at 1-month follow-up (14 TMS-EEG sessions in total). Active SNT progressively reduced cortical excitability at the treatment site, with significant decreases by day 3 in the early window component (−27.9%; P < 0.01), while no changes were observed at the vertex control site. Site-specific comparisons confirmed early window reductions only at the left dorsolateral prefrontal cortex (t₂₂ = −3.82; P < 0.001). SNT also selectively decreased estimated medial prefrontal source activity consistent with the subgenual anterior cingulate cortex (sgACC) across sessions (F₁₃,₂₂₂ = 4.93; P < 0.001), with effects persisting at 1-month follow-up. In an exploratory analysis in the active group (n = 12), higher baseline estimated sgACC source activity was associated with greater clinical improvement (r = −0.67; P = 0.023); although promising, the latter preliminary finding requires replication in larger, adequately powered samples before predictive utility can be established. These findings indicate that SNT induces progressive, site-specific cortical modulation and selective downstream effects on estimated sgACC source activity. Early cortical excitability changes represent candidate neurophysiological markers of SNT response, while the observed association between baseline sgACC activity and clinical outcome, while preliminary, motivates prospective investigation of subcortical source activity as a potential predictor of treatment response in larger trials. ClinicalTrials.gov Identifier: NCT03068715.